Pengaruh Product Brand Loyalty dan Purchase Decision Sepeda Motor: - Wahyu Goesty Perdana; Ida Bagus Nyoman Udayana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This research is testing the influence between product brand loyalty and automotive customer purchasing decisions. The study focused on a comparative analysis of two well-known motorcycle brands, namely YAMAHA and HONDA and the various influences on loyalty. A cross-sectional quantitative research design was used in this study. In today's competitive business world, now most of the marketers and manufacturers of various brands have faced many variables in which they can not only influence the purchasing decisions of their customers but also secure their buying preferences. The variables used and relevant to this research are product brand loyalty, perceived quality, price, and purchasing decisions. The findings of this study indicate that these variables play an important role in improving the purchasing decisions of automotive customers and hence, increasing sales, growth and profitability of automotive companies. These companies end up building long-term relationships with their current and future car users by building strong brands. Keywords: Product Brand Loyalty, Purchase Decision, Price Perception, Quality, Automotive Industry